(untitled) (Theatrum historiae, 2015)
Through analysing the processional veneration of the Eucharist in Vienna, this study re-assesses and differentiates the existing theories on the socio-cultural roles of Central European Corpus Christi processions in the context of one of the most significant residential and capital cities of the Holy Roman Empire. After presenting a historiographical and methodological contextualisation the study scrutinizes Viennese Eucharistic marches in a longue durée approach, i.e. reaching from the thirteenth until the sixteenth century. As shown through a qualitative sequence of case studies, the form of Eucharistic processions in Vienna was neither an act of unity, nor a value-free tool of religious thoughts. On the contrary, the regulations and orders of marches always involved acts of power from external authorities (clerical, archducal, academic and so on) imposing their political, social and cultural agenda on non-ndividualized groups of people. In this sense, the way of celebrating the feast in festive trains was actually in itself continuously compromising the original medieval mission of the cult and so became a perfect tool of early modern Catholic reform.